Drug-Eluting Stent vs Percutaneous Transluminal Angioplasty for Treatment of Femoropopliteal In-Stent Restenosis: Results From a Retrospective 1-Year Multicenter Study. (August 2016) - Murata, Naotaka; Takahara, Mitsuyoshi; Soga, Yoshimitsu; Nakano, Masatsugu; Yamauchi, Yasutaka; Zen, Kan; Kawasaki, Daizo; Yokoi, Hiroyoshi; Tosaka, Atsushi; Tanaka, Nobuhiro; Iida, Osamu
Purpose: To compare drug-eluting stent (DES) implantation with percutaneous transluminal angioplasty (PTA) in the treatment of femoropopliteal in-stent restenosis (ISR).Methods: A comparison was performed of data from 112 ZEPHYR registry patients (mean age 74±9 years; 60 men) with 119 femoropopliteal ISR lesions treated with a drug-eluting stent (Zilver PTX) with historical data from 116 patients (mean age 72±8 years; 83 men) with 133 lesions treated with PTA. The patients were stratified for analysis by lesions with (101/252, 40%) and without (n=151) in-stent occlusion. The primary outcome measure was the 1-year incidence of recurrent restenosis; the secondary outcome was major adverse limb events (MALE). Multivariate logistic regression analysis was performed to look for any independent association of DES implantation with 1-year recurrent restenosis in the respective subgroups; results are presented as the odds ratio (OR) and 95% confidence interval (CI).Results: In the subgroup without in-stent occlusion, there was no significant difference between DES and PTA in the 1-year incidence of recurrent restenosis (40.5% vs 45.7%, p=0.583, respectively) or MALE (27.8% vs 20.7%, p=0.322, respectively). However, in the subgroup with in-stent occlusion, DES implantation was associated with significantly lower incidences of recurrent restenosis (44.1% vs 90.3% for PTA, p<0.001) and MALE (25.5% vs 53.6% for PTA, p<0.001). Multivariate analysis confirmed that DES implantation had a significant independent negative association with the risk of recurrent restenosis in the subgroup with occlusion (OR 0.2, 95% CI 0.1 to 0.6, p=0.006).Conclusion: DES implantation may be more effective than PTA in the management of femoropopliteal ISR with occlusion, but equally effective to PTA in nonocclusive ISR lesions. These results require confirmation in prospective randomized studies.